Answer:
![f(x)=(x-1)\,(x-3)\.(x+2)](https://img.qammunity.org/2021/formulas/mathematics/college/ldhdhxq1cozlyn117pkm7v9fi0kuoi6qhf.png)
which agrees with the first answer shown in the list of possible options.
Explanation:
Notice that there are three roots for this polynomial clearly shown on the graph's crossings of the x axis: x = 1, x = 3, and x = -2.
Therefore, based on such, we can write three binomial factors of the form
for the polynomial:
![f(x)=(x-1)\,(x-3)\.(x-(-2))=(x-1)\,(x-3)\.(x+2)](https://img.qammunity.org/2021/formulas/mathematics/college/zz0x5bztpxrilu0ts0jjszri5tjmf1j9vy.png)